Transforming growth factor-β signaling pathway-associated genes SMAD2 and TGFBR2 are implicated in metabolic syndrome in a Taiwanese population. Issue 1 (December 2017) - Lin, Eugene; Kuo, Po-Hsiu; Liu, Yu-Li; Yang, Albert; Tsai, Shih-Jen
Abstract The transforming growth factor-β (TGF-β) signaling pathway and its relevant genes have been correlated with an increased risk of developing various hallmarks of metabolic syndrome (MetS). In this study, we assessed whether the TGF-β signaling pathway-associated genes of SMAD family member 2 (SMAD2 ), SMAD3, SMAD4, transforming growth factor beta 1 (TGFB1 ), TGFB2, TGFB3, transforming growth factor beta receptor 1 (TGFBR1 ), andTGFBR2 are associated with MetS and its individual components independently, through complex interactions, or both in a Taiwanese population. A total of 3, 000 Taiwanese subjects from the Taiwan Biobank were assessed. Metabolic traits such as waist circumference, triglyceride, high-density lipoprotein cholesterol, systolic and diastolic blood pressure, and fasting glucose were measured. Our results showed a significant association of MetS with the two single nucleotide polymorphisms (SNPs) ofSMAD2 rs11082639 andTGFBR2 rs3773651. The association of MetS with these SNPs remained significant after performing Bonferroni correction. Moreover, we identified the effect ofSMAD2 rs11082639 on high waist circumference. We also found that an interaction between theSMAD2 rs11082639 andTGFBR2 rs3773651 SNPs influenced MetS. Our findings indicated that the TGF-β signaling pathway-associated genes ofSMAD2 andTGFBR2 may contribute to the risk of MetS independently and through gene–gene interactions.